GC-MS analysis of phytochemical compounds of Opuntia megarrhiza (Cactaceae), an endangered plant of Mexico - Cupido, Madeleyne; De-Nova, Arturo; Guerrero-González, María L.; Pérez-Vázquez, Francisco Javier; Méndez-Rodríguez, Karen Beatriz; Delgado-Sánchez, Pablo (PeerJ Organic Chemistry, 2022)
Opuntia megarrhiza is an endemic plant used in Mexican traditional medicine for the treatment of bones fractures in humans and domestic animals. One of the most used technique for the detection and characterization of the structure of phytochemical compounds is the Gas Chromatography Coupled to Mass Spectrometry. The goals of the present study were to identify and characterize the phytochemical compounds present in wild individuals of O. megarrhiza using this analysis. We used chloroform and methanol extracts from cladodes, and they were analyzed by gas chromatography-electron impact-mass spectrometry. We obtained 53 phytochemical compounds, 19 have been previously identified with some biological activity. Most of these compounds are alkanes, alkenes, aromatic hydrocarbons, fatty acids, and ketones. We detected some fragmentation patterns that are described for the first time for this species. The variety of metabolites presents in O. megarrhiza justifies the medicinal use of this plant in traditional medicine and highlight it as a source of phytochemical compounds with potential in medicine and biotechnology.
Keywords: Bioprospection; Endemic; Metabolites; Phytochemicals screening